Equation of state and thermodynamic properties of BCC metals - Vu Van Hung, N.T. Hoa; Jaichan Lee (Universitas Gadjah Mada, 2006)
The moment method in statistical dynamics is used to study the equation of state and thermodynamic properties of the bcc metals taking into account the anharmonicity effects of the lattice vibrations and hydrostatic pressures. The explicit expressions of the lattice constant, thermal expansion oefficient, and the specific heats of the bcc metals are derived within the fourth order moment approximation. The termodynamic quantities of W, Nb, Fe,and Ta metals are calculated as a function of the pressure, and they are in good agreement with the corresponding results obtained from the first principles calculations and experimental results. The effective pair potentials work well for the calculations of bcc metals.